1970
DOI: 10.2337/diab.19.10.719
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Pernicious Anemia

Abstract: From 1959 to 1968, thirty-six cases of pernicious anemia (PA) were noted in 11,144 patients with diabetes mellitus (DM) at the Joslin Clinic (incidence 3.2/1,000). Of the thirty-six, only one was not insulin dependent. The female to male ratio was 7:5. Age ranged from thirty-four to eighty-one years. In twenty-eight patients with DM, a mean period of 12.6 years elapsed from time of diagnosis of diabetes mellitus to development of PA. In eight, PA preceded DM by a mean period of 6.6 years. Vitamin B12 deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Moreover, IDDM patients without clinical manifestations of organspecific autoimmune disease and their relatives have a high prevalence of thyroid microsomal, gastric parietal, and adrenal antibodies that support an autoimmune etiology for IDDM (5)(6)(7)(8)37). Moreover, IDDM patients without clinical manifestations of organspecific autoimmune disease and their relatives have a high prevalence of thyroid microsomal, gastric parietal, and adrenal antibodies that support an autoimmune etiology for IDDM (5)(6)(7)(8)37).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, IDDM patients without clinical manifestations of organspecific autoimmune disease and their relatives have a high prevalence of thyroid microsomal, gastric parietal, and adrenal antibodies that support an autoimmune etiology for IDDM (5)(6)(7)(8)37). Moreover, IDDM patients without clinical manifestations of organspecific autoimmune disease and their relatives have a high prevalence of thyroid microsomal, gastric parietal, and adrenal antibodies that support an autoimmune etiology for IDDM (5)(6)(7)(8)37).…”
Section: Discussionmentioning
confidence: 97%
“…Clinically and serologically, pernicious anaemia is associated with diabetes (Root, 1931;Arepakis, Bock & Williams, 1963;Moore & Neilson, 1963;Irvine & Davies, 1963;Ungar et al, 1968;Munichoodappa & Kozak, 1970) and with auto-immune thyroiditis (Irvine, Davies & Delmore, 1962;Doniach, Roitt & Taylor, 1963;Tudhope & Wilson, 1960). Serologically, there is an association between auto-immune thyroiditis and diabetes (Petit, Landing & Guests, 1961;Landing et al, 1963;Simkins, 1968;Irvine et al, 1970) but no definite clinical relationship has been reported to substantiate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…This interest results from the occasional clinical association of diabetes and autoimmune diseases of the ad renal [13]. thyroid [14,15], and hemato poietic tissues [16], the increased frequency of antibodies to thyroid and gastric parietal cells among diabetics [17,18]. the presence of islet cell cytoplasmic and surface antibodies in the serum of recently diagnosed type I dia betics [19][20][21], the existence of HLA-linked and properdin factor B (BO genes [22][23][24][25], the suggestion that suppressor T cell generation is defective in type I diabetes [26], the evi dence of increased numbers of circulating lapositive T lymphocytes [27] and the observa tion of Gepts [28] and others of a striking lymphocytic infiltration of the pancreatic is lets (insulitis) in recently diagnosed type 1 di abetics.…”
Section: Introductionmentioning
confidence: 99%